Risk Determinants in the Evaluation of Shares in the Colombian Market: Multifactor Comparative Model - Carmona Muñoz, Diana M.; Criollo Obando, Cielo P. (Cuadernos de Administración, 2015)
This article is based on the interest of presenting research results aimed at approaching the possible sources of market risk that may particularly influence on the yields of shares traded in the General Index of the Colombian Stock Exchange (IGBC, for the term in Spanish), hence, an approach is made at models of multiple factors to characterize these behaviors through the methodology of principal asymptotic components (PAC). In the implementation of the univariate and multivariate models two scenarios are worked; the first related to estimations from a rate free of short-term risk (Reference Bank Index –IBR, for the term in Spanish) and a rate free of long-term risk (TES Julios of 2020), whose results generated lead to the conclusion that the models behave better in short-term scenarios and that the best model for prognosis of return on variable equity in Colombia is still the single-factor model represented by the market risk. This research permitted delving deeper into recognizing the shares market in Colombia and contributes to the construction of databases that serve as information source and input for further research interests, as in the construction of the historical dividends of shares between 2007 and 2012; information the market does not have totally available and which permits evaluating assets in much more adjusted manner.